Comparative Study of Flavonoids in Licorice Fibers Growing in Various Soil Conditions (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The content of quercetin in the fibers of licorice plant growing in different regions has been investigated by the method of high-performance liquid chromatography (HPLC). The soil composition of the territories and the amount of Cl- and SO42- ions were determined using a spectrophotometer of the DR-3900 brand (Germany). Using the example of quercetin, it was found that the amount of flavonoids in plant tissues changes under the influence of external factors. As a result, the increased content of phenolic compounds in the plant under the influence of various environmental factors of the plant organism performs the function of protecting the plant from environmental factors.